Multidimensional poverty in Salvador diminished? Evidence based on a spatial approach - Santos, Eli Izidro dos; Barreto, Ricardo Candéa Sá; Carvalho, Ícaro Célio Santos de (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
This article aimed to analyze multidimensional poverty in the districts of Salvador. In calculating the Poverty Index (IP), not only income but also other variables were considered that reflect citizens’ deprivation. Salvador’s districts were organized according to poverty rankings that were, in comparison to the Human Development Index (HDI), consistent with a spatialized study of poverty in the capital of Bahia, in addition to showing a reduction of 59.91% between 2000 and 2010. Also, low and high levels of poverty were found in several areas of the city, especially in the north. Using a spatial econometric model pointed out the poverty determinants for the years 2000 and 2010, whose influence was negative for average income and longevity, whereas infant mortality, illiteracy, and income inequality had a positive influence.